PHYSICAL EDUCATION LEARNING DESIGN THROUGH TRADITIONAL BOXING 'SAGI' BASED ON TUTORIAL VIDEOS TO ENHANCE STUDENTS' CHARACTER EDUCATION - Wani, Bernabas (JURNAL EDUSCIENCE, 2025)
Purpose – The objectives of this study are: a) To develop a physical education learning design based on Sagi traditional boxing using video tutorial media, b) To enhance students' character education through the implementation of Sagi boxing, which includes values such as discipline, courage, and cooperation, c) To test the effectiveness of video tutorials as a medium for teaching the basic techniques of Sagi boxing to students.Methodology— The stages used in this study include Analysis, Design, Development, Implementation, and Evaluation. The data collection techniques applied consist of documentation and questionnaire distribution. The validation process for the video media was conducted through assessments by subject matter experts, instructional design experts, and instructional media specialists. The data obtained were analyzed using both qualitative and quantitative descriptive approaches.Findings – The study's results, based on expert responses, were as follows: Subject Matter Expert (91%, Very Good), Instructional Media Expert (94%, Very Good), and Instructional Design Expert (95%, Very Good). During the development process, improvements were made to enhance the quality of the instructional design for physical education, based on the traditional "Sagi" boxing method, supported by video tutorials aimed at strengthening students' character education, as informed by expert feedback.Contribution— This study is significant because it provides valuable insights for education managers, especially in schools that implement physical education, to apply ADDIE model-based evaluations in order to enhance the effectiveness and sustainability of developing physical education learning designs through the traditional "Sagi" boxing, supported by video tutorials, to strengthen students’ character education in schools.